Use of Moringa oleifera leaves (sole or combined with concentrate) in rabbit feeding: Effects on performance, carcass characteristics and meat quality attributes. (April 2023) - Bhatt, R.S.; Sarkar, Srobana; Sharma, S.R.; Soni, Arvind
Abstract: Sixty Chinchilla rabbits (28 days old) were divided into three equal groups ( n = 20). Rabbits in MOL0 (control) were fed pellets containing 700 g cowpea hay/kg pellet as forage source, whereas rabbits in MOL700 and MOL950 were fed pellets containing 700 and 950 g moringa leaves/kg feed pellets, respectively. Average daily gain and feed conversion ratio was comparable in MOL700 and MOL0, however, it was higher in MOL950. Among the carcass traits, dressing percent was higher while, chilling loss was lower in MOL700 treatment. The Longissimus thoracis muscle of rabbits fed moringa leaves containing pellets (MOL700 and MOL950) had lower saturated fatty acid content, higher C18:3n-3 and total n-3 fatty acids along with lower thrombogenic index value. Hence, incorporating moringa leaves at 70% level is beneficial in terms of improved growth performance and functional attributes of meat than diet- containing sole moringa leaves.